The philosophy of mind and cognition - Braddon-Mitchell, David (Blackwell Pub., 2007)
David Braddon-Mitchell and Frank Jackson's popular introduction to philosophy of mind and cognition is now available in a fully revised and updated edition. * Ensures that the most recent developments in the philosophy of mind and cognitive science are brought together into a coherent, accessible whole. * Revisions respond to feedback from students and teachers and make the volume even more useful for courses. * New material includes: a section on Descartes' famous objection to materialism; extended treatment of connectionism; coverage of the view that psychology is autonomous; fuller discussion of recent debates over phenomenal experience; and much more.